The GNB3 c.825C>T (rs5443) polymorphism and protection against fatal outcome of corona virus disease 2019 (COVID-19) - Möhlendick, Birte; Schönfelder, Kristina; Zacher, Christoph; Elsner, Carina; Rohn, Hana; Konik, Margarethe J.; Thümmler, Laura; Rebmann, Vera; Lindemann, Monika; Jöckel, Karl-Heinz; Siffert, Winfried (Frontiers in Genetics, 2022)
Background and aims Albeit several factors which influence the outcome of corona virus disease (COVID-19) are already known, genetic markers which may predict the outcome of the disease in hospitalized patients are still very sparse. Thus, in this study we aimed to analyze whether the single nucleotide polymorphism (SNP) rs5443 in the gene GNB3, which was associated with higher T cell responses in previous studies, might be a suitable biomarker to predict T cell responses and the outcome of COVID-19 in a comprehensive German cohort. Methods We analyzed the influence of demographics, pre-existing disorders, laboratory parameters at the time of hospitalization as well as GNB3 rs5443 genotype in a comprehensive cohort (N = 1570) on outcome of COVID-19. In a sub cohort we analyzed SARS-CoV-2-specific T cell responses and associated GNB3 rs5443 genotypes. We investigated the influence of all factors on COVID-19 fatality in a multivariable analysis. Results We found a younger patient age, normotension or absence of diabetes mellitus or cardiovascular diseases, normal blood cell counts as well as low inflammatory markers at hospital admission were protective factors against fatal course of disease. Additionally, the rs5443 TT genotype was significantly associated with protection against COVID-19 fatality (OR: 0.60, 95 % CI: 0.40 - 0.92, P = 0.02). We also observed significantly increased SARS-CoV-2-specific T cell responses in rs5443 TT genotype carriers (P = 0.01). Although we observed a significant association of the factors described above in univariate analysis only a younger age of the patients, normal blood cell counts and the GNB3 rs5443 TT genotype remained independent predictors against COVID-19 fatality in multivariable analyses. Conclusion Immutable predictors for COVID-19 fatality are relatively rare. In this study we could show that the TT genotype of the SNP rs5443 in the gene GNB3 is associated with protection against COVID-19 fatality. It was as well correlated to higher SARS-CoV-2-specific T cell responses, which could result in a milder course of disease in those patients. Based on those observations we hereby provide a further prognostic biomarker, which might be used in routine diagnostics as a predictive factor for COVID-19 mortality already upon hospitalization.